Cooperation between p53 and the telomere-protecting shelterin component Pot1a in endometrial carcinogenesis - Akbay, E A (Nature Publishing Group, 2013)
Type II endometrial cancer (EMCA) represents only 10% of all EMCAs, but accounts for 40% of EMCA-related mortality. Previous studies of human tumors have shown an association between Type II tumors and damaged telomeres. We hypothesized that the lack of murine Type II EMCA models is due to the extremely long telomeres in laboratory mouse strains. We previously showed that telomerase-null mice with critically short telomeres developed endometrial lesions histologically resembling endometrial intraepithelial carcinoma (EIC), the accepted precursor for Type II EMCA. However, these mice did not develop invasive endometrial adenocarcinoma, and instead succumbed prematurely to multi-organ failure. Here, we modeled critical telomere attrition by conditionally inactivating Pot1a, a component of the shelterin complex that stabilizes telomeres, within endometrial epithelium. Inactivation of Pot1a by itself did not stimulate endometrial carcinogenesis, and did not result in detectable DNA damage or apoptosis in endometrium. However, simultaneous inactivation of Pot1a and p53 resulted in EIC-like lesions by 9 months indistinguishable from those seen in late generation telomerase-null mice. These lesions progressed to invasive endometrial adenocarcinomas as early as 9 months of age with metastatic disease in 100% of the animals by 15 months. These tumors were poorly differentiated endometrial adenocarcinomas with prominent nuclear atypia, resembling human Type II cancers. Furthermore, these tumors were aneuploid with double-stranded DNA breaks and end-to-end telomere fusions and most were tetraploid or near-tetraploid. These studies lend further support to the hypothesis that telomeric instability has a critical role in Type II endometrial carcinogenesis and provides an intriguing in-vivo correlate to recent studies implicating telomere-dependent tetraploidization as an important mechanism in carcinogenesis.